Mineralizable soil nitrogen: amounts and extractability ratios - Paul, Eldor A., author; Juma, N. G., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 1984)
Studies were conducted on a 15N-labeled Weirdale loam, a Dark Gray Chernozemic soil (Boralfic Boroll) to (i) determine the amounts of N released by several methods previously used to obtain an estimate of potentially mineralizable N, (ii) determine their 15N enrichment and extractability ratios, and (iii) compare the results from the above with the N mineralized during incubation and NH+4 released by the chloroform fumigation incubation technique. The NH+4-N accumulated during 10 d in fumigated soils accounted for ∼1% of total N, was highly labeled, and had extractability ratios of 6.6 to 7.4. These ratios were similar to ones obtained for N mineralized during incubation of unfumigated soils. Ammonium-N extracted with dilute acidic permanganate solution (0.01M KMnO4 in 0.1 or 0.5M H2SO4) accounted for 0.72 to 0.84% of total N and had extractability ratios ranging from 3.4 to 3.9. A stronger solution of acidic permanganate extracted more N that was less enriched. Dilute sulfuric acid extracted NH+4 and organic N that had extractability ratios of < 3. Ammonium-N released by autoclaving the soil accounted for ∼1% of total N and had extractability ratios ranging from 0.6 to 0.9. Acid hydrolysis showed that 72% of total N was hydrolyzable, 32% was amino acid-N and 20% was NH+4 released on hydrolysis. The extractability ratio for NH+4 released on hydrolysis was 1.7 and was significantly (P < 0.01) greater than extractability ratios of hydrolyzable N and amino acid-N. The similarity and high extractability ratios of NH+4 released after fumigation and NO-3-N accumulating during aerobic incubation indicated that the fumigation extracted a biologically meaningful fraction. The biomass was responsible for only 15 to 25% of the net N mineralized during a 12-week incubation. Results indicated that (i) extraction of a highly labeled N pool in soil can only partly explain the source of N being mineralized, (ii) N is mineralized from several pools, and (iii) there is a remote possibility that a single extractant can extract the variety of N compounds undergoing mineralization and immobilization in soil.
Keywords: biomass N; N supply power; nonbiomass active N; total N; N availability ratios; NO; active N phase